The Anatomical Society's core anatomy syllabus for undergraduate nursing. Issue 5 (7th February 2018) - Connolly, S. A.; Gillingwater, T. H.; Chandler, C.; Grant, A. W.; Greig, J.; Meskell, M.; Ross, M. T.; Smith, C. F.; Wood, A. F.; Finn, G. M.
Abstract: The Anatomical Society has developed a series of learning outcomes in consultation with nursing educators delivering anatomical content to undergraduate (preregistration) nursing students. A Delphi panel methodology was adopted to select experts within the field that would recommend core anatomical content in undergraduate nursing programmes throughout the UK. Using the Anatomical Society's Core Gross Anatomy Syllabus for Medical Students as a foundation, a modified Delphi technique was used to develop discipline‐specific outcomes to nursing graduates. The Delphi panel consisted of 48 individuals ( n  = 48) with a minimum of 3 years' experience teaching anatomy to nursing students, representing a broad spectrum of UK Higher Education Institutions. The output from this study was 64 nursing specific learning outcomes in anatomy that are applicable to all undergraduate (preregistration) programmes in the UK. The new core anatomy syllabus for Undergraduate Nursing offers a basic anatomical framework upon which nurse educators, clinical mentors and nursing students can underpin their clinical practice and knowledge. The learning outcomes presented may be used to develop anatomy teaching within an integrated nursing curriculum.